Educating children through their parents to prevent child sexual abuse in Turkey. Issue 3 (4th December 2019) - Apaydın Cırık, Vildan; Efe, Emine; Velipaşaoğlu, Sevtap
Abstract: Purpose: The aims of this study were to train parents to recognize and prevent child sexual abuse (CSA); evaluate the problems encountered by parents; and evaluate the overall effectiveness of the CSA training program. Design and Methods: The study used a pretest/posttest design. The study was conducted with a sample of 58 children (aged 3‐6 years) and 64 parents. Findings: Children who received CSA prevention education from their parents demonstrated improved knowledge about private parts and about what they should do if they suspect sexual abuse. The parents stated that they encountered some problems (other family members objected to the child being given such training). Practise Implications: Children's risk of abuse may be reduced if their parents teach them about CSA correctly.